Students Ability in Producing the Sentences of Simple Present Tense at STMIK Musi Rawas - Herlina Herlina; Maria Ramasari (Linguistic, English Education and Art (LEEA) Journal, 2018)
This research aimed to find out the students ability in producing the sentences of simple present tense at STMIK Musi Rawas. The research was a qualitative study. As stated in findings, it interpreted that there were 34 students (62.91 percent) in the low category. Thus, there were 15 students (27.50 percent) in the good category. Finally, there were 5 students (9.59 percent) in the excellent category. Hence, it can be concluded that students ability in producing the sentences of simple present tense was still low. It showed that many students still got difficulties in producing the sentences of simple present tense especially for verb in third person singular as the subject pronoun. Keywords: students ability, simple present tense, sentences